PEMBUATAN MESIN KONDOM OTOMATIS: KAJIAN REFLEKTIF ILMU HUKUM TERHADAP ASPEK SEKSUALITAS MASYARAKAT - Raissa, Amanda; Kleden, Kristoforus Laga; Michael, Tomy (VYAVAHARA DUTA, 2020)
In Indonesia discussing sex is a taboo subject to talk about. Many families, educational institutions, even the government is very minimal or even does notprovide education about sex in early age to childrens and adolescents, so it cannot be denied that the lack of sex education causes many cases of women who become pregnant out of wedlock and also more people who contract sexually transmitted diseases.So in this writing the author examines the procurement of condom vending machines in the college environment that not only releases condoms but also some issues articles of various laws and regulations related to the aim of providing education about healthy and safe sex and giving reminders to young people about the consequences that will be faced if someone has sex outside of marriage. The method used in this writing is empirical juridical where the writer sees the reality and the facts that exist and integrates with the applicable legal norms. The results of this study that there are still many young people who ignore the importance of using condoms to prevent sexually transmitted diseases and consider sex education as a taboo even in educational institutions